Generalization of a Thiele fraction - Makarov, V. L.; Demkiv, I. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
A new type of the generalized integral chain fraction interpolation is proposed. It extends the Thiele type continued fraction interpolation to the class of non-linear functionals defined in an arbitrary linear topological space. We study two specific realizations of such interpolation process. One of them is a Thiele type continued fraction interpolation for functions with an arbitrary number of variables without any additional geometric constrains on the placement of interpolation points.